Comparison of γ-Oryzanol Content Using HPLC Profiling and Bioactivity in Three Indonesian Brown Rice (Oryza sativa L.) Varieties - Umar, Ja’far; Palis, Christine Natalia; Suyanto, Eko; Turhadi, Turhadi; Wihastuti, Titin Andri; Fatchiyah, Fatchiyah (Universitas Gadjah Mada, 2026)
Brown rice (BrR) is a nutrient-rich staple food and a potential source of γ-oryzanol, which has the potential to promote health effects in hypercholesterolemia. However, the availability and biological mechanism of γ-oryzanol in Indonesian BrR remain unexplored. This study aimed to characterize γ-oryzanol content in three Indonesian BrR varieties, Black Madras, Lawang, and UB BrR, and evaluate its biological functions for hypercholesterolemia. γ-Oryzanol was identified using HPLC, antioxidant activity by the ferric reducing antioxidant power (FRAP) method, and anticholesterol activity by the Lieberman-Burchard method. In silico analysis was performed to assess γ-oryzanol derivatives' interaction with microsomal triglyceride transfer protein (MTP). Black Madras BrR showed the highest γ-oryzanol content (0.3007 ± 0.0011 g). γ-Oryzanol was comprised of four main derivatives: cycloartenyl ferulate, 24-methylenecycloartanyl ferulate, campesteryl ferulate, and β-sitosteryl ferulate. Black Madras BrR exhibited strong antioxidant (IC50 18.89 ± 0.37 μg/mL) and anticholesterol (IC50 14.02 ± 0.23 µg/mL) activities. Docking simulations revealed that γ-oryzanol derivatives interact with MTP lipid-binding residues (Leu643, Ile666, Phe813, Val817) with the same binding energy as lomitapide. Molecular dynamics indicated γ-oryzanol stable interaction, closer to lomitapide. These findings proposed the potential bioactivity of γ-oryzanol from Black Madras BrR as antioxidant, anticholesterol, and a natural MTP inhibitor for hypercholesterolemia treatment.